The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1982-56762011000500003
|View full text |Cite
|
Sign up to set email alerts
|

Isoenzymatic characterization of Colletotrichum kahawae isolates with different levels of aggressiveness

Abstract: The hemibiotrophic fungus Colletotrichum kahawae is the causal agent of Coffee Berry Disease -CBD, an economically devastating disease restricted to Arabica coffee production in Africa. Understanding pathogen variability is crucial for the implementation of disease control measures. In this study, six isoenzymatic systems (esterase, acid and alkaline phosphatase, malate dehydrogenase, peroxidase and superoxide dismutase) were used to assess the genetic variation among 12 C. kahawae isolates (from different geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…The detached green berries and hypocotyls were inoculated using the techniques described by Loureiro et al . () and Figueiredo et al . (), respectively.…”
Section: Methodsmentioning
confidence: 85%
See 4 more Smart Citations
“…The detached green berries and hypocotyls were inoculated using the techniques described by Loureiro et al . () and Figueiredo et al . (), respectively.…”
Section: Methodsmentioning
confidence: 85%
“…Using this system, C. kahawae isolates were assigned into different classes and subclasses and in generally presented a similar classification to those previously attributed in other C. kahawae aggressiveness studies (Loureiro et al ., ; Pires et al ., ; Vieira et al ., ). Nevertheless, a few discrepancies were found for some isolates, such as Cam 1 which was classified as highly aggressive (Loureiro et al ., ), Que 2, Ang 6 and Zim 1 which were classified as low aggressive isolates (Pires et al ., ), and Zim 12 as moderately aggressive (Pires et al ., ). In the present study, these isolates revealed a different profile: Zim 1 and Ang 6 were classified as low‐moderate aggressive isolates, Que 2 and Cam 1 as high‐moderate aggressive isolate and Zim 12 as a high aggressive isolate.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations